Radical Literature and Cultural Validation: The Paradox of Merlin Radical Fiction - Carr, Graham (Labour / Le Travail, 1994)
The article reviews and comments on three books including "Out of Work," by Margaret Harkness, "The Story of a Modern Woman," by Ella Hepworth Dixon and "Sandwichman," by Walter Brierley.
Keywords: BOOKS – Reviews; BRIERLEY; Walter; DIXON; Ella Hepworth; HARKNESS; Margaret; Nonfiction; OUT of Work (Book); SANDWICHMAN (Book); STORY of a Modern Woman; The (Book)